AB0021 Resistin Gene Transcription Is Regulated in Adaptive and Innate Immunity in Rheumatoid Arthritis. (15th July 2016) - Andersen, M.; Meyer, M.K.; Nagaev, I.; Nagaeva, O.; WIkberg, J.E.S.; Mincheva-Nilsson, L.; Andersen, G.N.
Abstract : Background: Resistin (RETN) was described in 2001 as an adipokine secreted by murine adipocytes resulting in insulin resistance. However, in man, adipocyte synthesis of RETN is controversial, while monocyte RETN production is well established (1). Curiously, RETN synthesis and its regulation in pathogenic immune cell subsets have not been examined in rheumatoid arthritis (RA), although blood RETN levels correlate to disease activity. In RA, -a risk factor for coronary artery disease (CAD), RETN might contribute to atherosclerosis. E.g. macrophage secreted RETN in atheromas, facilitates cholesterol uptake and plaque instability. Considering this, an in depth understanding of the regulation and effects of RETN synthesis in pathogenic immune cell subsets may provide clues to the aetiology of CAD, known to be associated with factors (high CRP, RF and ACPA), characterizing active RA. Objectives: The aim of our investigation was to explore whether RETN gene transcription in pathogenic cell subsets of innate and adaptive immunity is detectable and if present, amenable to TNFα inhibition (I) and correlated to important cytokines in RA. Methods: We examined the reaction of RETN gene transcription to TNFαI in CD14 + monocytes, CD4 + T helper (Th) lymphocytes (ly), CD8 + T cytotoxic (Tc) ly, and CD19 + B ly in RA patients, responding to adalimumab. Leukocyte subsets from 7 RA patients were isolated by Dynabeads before and 3 months after start of TNFαI. Total RNA was extracted and mRNAs for RETN and a panel of disease driving Th1, inflammatory and regulatory cytokines were measured by real-time qRT-PCR. Results: RETN gene transcription was present in al cell subsets and in CD14 + monocytes and CD4 + Th ly responded to TNFαI with a significant decrease. In CD14 + monocytes the RETN gene was transcribed to a significantly higher degree than in lymphocyte subsets of the adaptive immune system both before and during TNFαI. In active RA, prior to TNFαI, RETN and TGFβ mRNA levels correlated significantly in CD4 + Th ly (P=0.03), while in CD14 + monocytes fold change in TGFβ and RETN mRNAs due to TNFαI correlated highly significantly (P=0.01). Furthermore, RETN and IL-8 mRNA levels tended to correlate (P=0.06) in CD14 + monocytes prior to TNFαI. Conclusions: We here report regulated RETN gene transcription in human CD4 + Th ly as well as in CD14 + monocytes. Our results point at wider functions for RETN. Thus we found TNFαI regulated RETN gene transcription in CD4 + Th ly in RA, indicating a possible immune response directing role. In this aspect, our results are in concert with increased RETN mRNA correlating to CD4 + Th17 ly number in human cecum. The idea of RETN pleiotropic actions is further supported by the correlation to TGFβ transcription. RETN and TGFβ share a pathway for their synthesis and fibrogenic ability (2), on top TGFβ also has a prominent role in immune tolerance. The relation to IL-8 indicates influence on neutrophil trafficking (1). References: Nagaev I et al. Human resistin is an immune-derived proinflammatory cytokine targeting both leukocytes and adipocytes. PLoS One 2006 Dec 20;1:e30. Chemaly R et al. Differential patterns of replacement and reactive fibrosis in pressure and volume overload are related to the propensity for ischaemia and involve resistin. J Physiol 2013;59:5337–55 Disclosure of Interest: None declared